DRAMATURGY OF MIHAYL MOGILYANSKY: CONFLICTS AND CHARACTERS - Khorob S. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The features of conflicts and characters of the not popular Ukrainian writer Mihayla Mogilyansky are explored in the article. An author analyses these ideological aesthetically beautiful categories in plays „Mirage" „Tina" and „Tired", inscribing the adopted dramas to the dramaturgic-theatrical context of beginning of ХХ age - Ukrainian and Western European. It is first led to, that dramaticseats of Mihayla Mogilyansky is not simply the fact of historical and literary process in Ukraine, and there is the unordinary phenomenon of national-spiritual cultural space.